2021
DOI: 10.1177/0391398821995495
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical study of cervical spine: A Finite Element Analysis

Abstract: The biomechanical study helps us to understand the mechanics of the human cervical spine. A three dimensional Finite Element (FE) model for C3 to C6 level was developed using computed tomography (CT) scan data to study the mechanical behaviour of the cervical spine. A moment of 1 Nm was applied at the top of C3 vertebral end plate and all degrees of freedom of bottom end plate of C6 were constrained. The physiological motion of the cervical spine was validated using published experimental and FE analysis resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…This suggests that Group 2 is closer to the physiological cervical biomechanical characteristics; Group 1 and Group 2 had similar effects on the average intervertebral disc pressure at the intermedial level (C4/5). Considering the mobility of the intermedial intervertebral disc of Group 1 was higher than Group 2, the protective effect of Group 1 on the intermedial intervertebral disc might be achieved by increasing segmental ROM to buffer the intervertebral disc pressure [24].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This suggests that Group 2 is closer to the physiological cervical biomechanical characteristics; Group 1 and Group 2 had similar effects on the average intervertebral disc pressure at the intermedial level (C4/5). Considering the mobility of the intermedial intervertebral disc of Group 1 was higher than Group 2, the protective effect of Group 1 on the intermedial intervertebral disc might be achieved by increasing segmental ROM to buffer the intervertebral disc pressure [24].…”
Section: Discussionmentioning
confidence: 98%
“…Material properties and element types are shown in Table 2 [15,17,[21][22][23]. In these FEMs, the thickness of cortical shell and endplates was set as 0.4 mm [24]. As to the facet joint, the articular surface was covered with cartilage, which was assigned with nonlinear surface-tosurface contact; the thickness of cartilage and the gap were 0.5 mm [14].…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 A moment of 1 Nm is applied in all physiological motion. 2628 In all the loading protocols the inferior endplate of C6 level motion was fully constrained.…”
Section: Methodsmentioning
confidence: 99%
“…FEM can be used to examine the following issues relating to degenerative disc disease: (a) the etiology of intervertebral disc degeneration (IVDD), including biological and biomechanical pathogenesis, (b) the biology, biochemistry and biomechanics of IVDD, and (c) the examination of biological and surgical management for IVDD [37][38][39][40][41][42][43][44]. In particular, in a recent FEM study that ascertained the biomechanical consequences of a degenerated L4-L5 segment, it was found that abnormal loading and motion in the degenerated models enhanced degeneration in the neighboring normal segments [45,46].…”
Section: Degenerative Disc Diseasementioning
confidence: 99%